1996
DOI: 10.1055/s-2007-997593
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosteron- versus Gesamttestosteronwerte im Serum von Patienten mit Larynxkarzinomen und chronischer Laryngitis

Abstract: The average age of the cancer patients examined was 10 years higher than in the laryngitis group. The present results partially correspond to the reports in the endocrinological literature. Together with experimental results regarding the effects of pure substances of testosterone and dihydrotestosterone on permanent laryngeal cancer cell lines, the current results confirm the importance of the imbalance between testosterone and dihydrotestosterone as a cofactor in the development of squamous cell carcinomas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Decreased testosterone is linked to decreased lean body mass in the general population and in the head and neck cancer setting . Hypogonadism is prevalent in male patients with head and neck cancer . It is present during initial diagnosis, but also seems to persist in cancer survivors .…”
Section: Methodsmentioning
confidence: 99%
“…Decreased testosterone is linked to decreased lean body mass in the general population and in the head and neck cancer setting . Hypogonadism is prevalent in male patients with head and neck cancer . It is present during initial diagnosis, but also seems to persist in cancer survivors .…”
Section: Methodsmentioning
confidence: 99%
“…Despite a variety of factors known to promote malignant changes in the laryngeal mucosa (eg, tobacco smoke, excessive alcohol consumption, occupational exposure to dusts, gases, and smoke4, 16–18) these factors do not explain sufficiently the imbalance between the sexes in the occurrence of the disease. So far, the hypothesis of hormone dependency of laryngeal carcinoma has not been proved 10–12, 19–22…”
Section: Discussionmentioning
confidence: 99%
“…A range of studies describing sex hormone concentrations in patients with cancer of the larynx have not brought clear results. Some authors suggested hyperandrogenism or hypoandrogenism as factors predisposing to laryngeal carcinoma; others emphasized the role of an imbalance between total testosterone and DHT 11, 21. Fillipov et al23 found low levels of total testosterone in each of 166 examined patients.…”
Section: Discussionmentioning
confidence: 99%